Passages Explorations of the Contemporary City - Livesey, Graham (University of Calgary Press, 2004)
Informed by the work of writers such as Henri Lefebvre, Paul Ricoeur and Michel de Certeau, this collection of essays examines through multiple lenses eight topics related to the contemporary urban domain. The author employs powerful geographic and literary concepts such as space, narrative, and metaphor to interpret the often-bewildering complexity of the post-modern city. Recalling key aspects of our shared intellectual heritage, Passages seeks to demystify the structure and historical development of the contemporary city in an accessible, engaging style. Passages is indispensable for those examining the city from either the professional design or the cultural studies standpoint.